2012
DOI: 10.1074/jbc.m112.421503
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Phosphorylation of Ser21 and Ser83 during Nutrient-induced Activation of the Yeast Protein Kinase A (PKA) Target Trehalase

Abstract: Background: Activation of yeast trehalase has been a convenient read-out for nutrient signaling to PKA, but demonstration of phosphorylation in vivo is lacking.Results: Nutrient activation is associated with phosphorylation, but phosphorylation is not enough for activation.Conclusion: Nutrient activation of trehalase is a reliable read-out for nutrient activation of PKA in vivo.Significance: Nutrient-sensing mechanisms can be identified using trehalase activation as a read-out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 62 publications
3
73
0
Order By: Relevance
“…Holt et al found Nth1-Ser66 to be the third-most strongly CDK-responsive residue in the proteome. PKA activates Nth1 by phosphorylation on Ser20, 21, 60 and 83 (Schepers et al, 2012; Veisova et al, 2012), so it seemed plausible that phosphorylation of Ser66 in the middle of this cluster of PKA sites might also activate Nth1. Likewise, three phosphoproteomic studies (Albuquerque et al, 2008; Soulard et al, 2010; Swaney et al, 2013) showed that Ser19 of Gph1 ( S PHQ) is phosphorylated in vivo .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Holt et al found Nth1-Ser66 to be the third-most strongly CDK-responsive residue in the proteome. PKA activates Nth1 by phosphorylation on Ser20, 21, 60 and 83 (Schepers et al, 2012; Veisova et al, 2012), so it seemed plausible that phosphorylation of Ser66 in the middle of this cluster of PKA sites might also activate Nth1. Likewise, three phosphoproteomic studies (Albuquerque et al, 2008; Soulard et al, 2010; Swaney et al, 2013) showed that Ser19 of Gph1 ( S PHQ) is phosphorylated in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, high PKA activity leads to Gph1 phosphorylation on T31, activating the enzyme and glycogen breakdown (Lin et al, 1996). PKA may also activate neutral trehalase (Nth1) by phosphorylating S20, S21, S60 and S83, with S60 and S83 apparently most important (Schepers et al, 2012; Veisova et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…We used the well-established downstream target trehalase as a direct read-out for PKA activity 1522. This showed that very low iron concentrations, as low as 100 nM, in the form of FeCl 3 or FeCl 2 were able to trigger a rapid, transient increase in trehalase activity in cells starved for two days for iron using the BPS chelator (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The yeast Nth1, compared with trehalases from prokaryotic and higher eukaryotic organisms, exhibits distinct domain structure and regulation, as its activity is triggered by association with the 14-3-3 protein, which recognizes two phosphorylated motifs within the N-terminal extension of Nth1 (20)(21)(22)(23). Previous studies have suggested an allosteric mechanism, whereby 14-3-3 protein binding affects the structure of the catalytic domain of pNth1 , with Nth1-CaBD (the EF-hand-like motif-containing domain) being the intermediary between 14-3-3 and the catalytic domain (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…1A), indicating significantly different regulation (17)(18)(19). It was subsequently shown that S. cerevisiae Nth1 is indeed activated in a PKA-and calcium-dependent manner in a process that requires interaction with the 14-3-3 protein through motifs containing phosphoserines pS60 and pS83 (20)(21)(22)(23). Significance 14-3-3 proteins are conserved scaffolding proteins expressed in all eukaryotic cells, where they regulate the function of several hundreds of partner proteins by constraining their conformation.…”
mentioning
confidence: 99%